China in the world an anthropology of Confucius Institutes, soft power, and globalization - Hubbert, Jennifer Ann (University of Hawaiʻi Press, 2019)
"Confucius Institutes, the language and culture programs funded by the Chinese government, have been established in more than 1500 schools worldwide since their debut in 2004. A centerpiece of China's soft power policy, they represent an effort to smooth China's path to superpower status by enhancing its global appeal. Yet Confucius Institutes have given rise to voluble and contentious public debate in host countries, where they have been both welcomed as a source of educational funding and feared as spy outposts, neocolonial incursions, and obstructions to academic freedom. China in the World turns an anthropological lens on this most visible, ubiquitous, and controversial globalization project in an effort to provide fresh insight into China's shifting place in the world."--Back cover.